The Effect of Internet Banking, Size, NPL and CAR on Net Interest Margin (NIM) and Banking Efficiency in Indonesia During Covid-19 Pandemic - Putri, Riescy Nanda; Yafiz, Ifa Adina (International Journal of Economic, Business & Applications, 2023)
This study analyzes the effect of Internet Banking, Size, NPL and CAR on profitability and efficiency of Indonesian banking as proxied by Net Interest Margin (NIM) and Operating Costs and Operating Income (BOPO) during the pandemic COVID-19 (2020-2021). This study also looks at the effect of Firm Size (Size), Capital Adequacy Ratio (CAR) and Non Performing Loans (NPL) on profitability and efficiency in that period. The population is Indonesian conventional banks registered in Bank Indonesia (2020-2021), totaling 117 banks. The sample was determined using purposive sampling, 62 banks in total. The method used is multiple linear regression with dummy variables. The results showed that internet banking had a significant negative effect on NIM and internet banking had a significant positive effect on BOPO. Another variable is size has no effect on NIM and has a significant negative effect on BOPO. CAR has no effect on NIM and has a significant negative effect on BOPO. Meanwhile, NPL has a significant negative effect on NIM and a significant positive effect on BOPO. The factor that has the biggest influence on NIM is NPL. While the factors that affect BOPO more are CAR and NPL. Banks are expected to pay more attention to the level of capital adequacy, credit risk and the level of total assets to increase bank profitability and efficiency in the future in dealing with the pandemic situation.